Winning the start-up game: Antecedent factors that impact success for small and medium-sized enterprises in Malaysia - Stephanie Rosnah Kenteh @ Kinti; Siri Roland Xavier; Hj Mustafa Bin Dakian (Journal of Management and Science, 2025)
This research paper aims to explore and determine critical success factors, barriers, and solutions for successful Small and Medium-sized Enterprise (SME) start-up projects in Malaysia. Based on previous research, the following hypotheses will be further analysed to determine the relationship between age, gender, success factors, barriers, and solutions for SME start-up projects in Malaysia. By identifying the critical success factors (CSFs), barriers, and solutions, this research gap can help new ventures understand the attributes necessary for success and overcome common obstacles. The research methodology of study is to apply the cross sectional research design which the analysis of homogeneity in perceptions concerning age group and gender provides a valuable tool for entrepreneurs to tailor their approach to different demographics. The sampling design/techniques is clustering random sampling. Based on the survey data of 143 respondents and analysis using the Statistical Package for Social Science (SPSS), the most critical success factor for SMEs is good management skills. The data analysis and research findings are Success factors, it was observed that the "Financing skill" was a statistically significant factor that contributed to the success of male-owned businesses. The test yielded a U-value of 1243 and a p-value of 0.04, which indicates that male respondents placed a higher level of importance on their financial skills than their female counterparts did. It is worth noting that the standard significant level effect was set at p ≤ 0.05, which means that the observed difference in financing skill between male and female respondents was statistically significant and not due to chance. The theoretical and practical implications of this research will determine the critical success factors of SME start-up projects in Malaysia, providing valuable knowledge to entrepreneurs and increasing their chances of success. Additionally, the study will propose solutions to improve the success rate of SME start-up projects in Malaysia. Finally, The ultimate goal of this study is to provide a comprehensive report on SME start-up projects that covers all the current issues new entrepreneurs face. The contributions of the study has successfully achieved its objectives of identifying the factors that contribute to success and the challenges that entrepreneurs face in SME start-ups in Malaysia and provides valuable insights to new entrepreneurs looking to reduce start-up failure rates. Overall, this research is a constructive guide for SMEs looking to succeed in Malaysia.